572 Fibroblast activating protein (FAP)-targeting IL-12 (anti-FAP/IL-12) TMEkine™ potentiates anti-cancer effects in preclinical cancer models. (9th November 2020) - Kim, Donggeon; Lee, Dahea; Ryu, Soomin; Byeon, Yeongseon; Pyo, Kyoung-Ho; Kim, Jae-Hwan; Lee, Seul; Kim, Dong Kwon; Lee, Eun Ji; Oh, Seung Yeon; Cho, Byoung Chul; Lee, Byoung Chul
Abstract : Background: Although cancer immunotherapy showed promising results in hematological malignancies, it has come up with relatively low tumor response for many solid tumors partly due to immune-suppressive tumor microenvironment (TME). Because of the immune-suppressive nature of TME, TME has been an active area of research and therapeutic target for restoring immune system and subsequent tumor growth inhibition. Among the many components in TME, cancer-associated fibroblasts (CAFs) are one of the key cell components of TME where one of the promising solid-tumor TME marker, fibroblast-activating protein (FAP) is highly expressed. Here we have developed an antibody-cytokine fusion protein from our TMEkine™ platform containing anti-FAP and IL-12. Our TMEkine™ (anti-FAP-IL-12) molecule induced strong anti-cancer effects in preclinical solid tumor models by immune-modulation. Methods: IL-12 cytokine was mutated in TMEkine™ (anti-FAP-IL-12) to reduce systemic toxicity and its binding affinity was tested to FAP and IL-12 receptor. The anti-tumor activity of anti-FAP-IL-12 was investigated on CT26 (murine colorectal cancer) syngeneic mouse models with/without NIH-3T3 (murine fibroblast). Additionally, mice showing complete response after anti-FAP-IL-12 administration were re-injected CT26 with/without 4T1 cells for re-challenge study to monitor long-term durable response generated from the initial immune activation. Results: We showed that TMEkine™ (anti-FAP-IL-12) interacts with FAP and IL-12 receptor. IL-12 activity was attenuated by our IL-12 mutants. We also showed that TMEkine™ (anti-FAP-IL-12) induced IFN-γ from primary human T cells and NK cells. TMEkine™ (anti-FAP-IL-12) administration resulted in significant reduction of the tumor burden in both CT26+NIH-3T3/FAP+ and CT26/FAP+ models. In the re-challenge experiments, CT26 tumor growth was inhibited significantly compared to 4T1 tumor suggesting memory immune response was generated in TMEkine™ (anti-FAP-IL-12) treated mice. Conclusions: These findings provide evidences that the treatment of anti-FAP/IL-12 TMEkine™ induced anti-cancer effects without serious adverse effects. Anti-FAP/IL-12 has a strong potential to provide a therapeutic option for cancer-specific immunomodulator and cancer cell eradication.